Quantifying the inflationary impact of fiscal stimulus under supply constraints - Julian Di Giovanni; Sebnem Kalemli-Ozcan; Álvaro Silva; Muhammed Ali Yıldırım (Federal Reserve Bank of New York, 2023)
This paper builds on Baqaee and Farhi (2022) and di Giovanni et al. (2022) to quantify the contribution of fiscal policy to U.S. inflation over the December 2019-June 2022 period. Model calibrations show that aggregate demand shocks explain roughly two-thirds of total model-based inflation, and that the fiscal stimulus contributed half or more of the total aggregate demand effect.
Keywords: E23; E31; E32; 330; inflation; fiscal policy; supply constraints; Finanzpolitik; Wirkungsanalyse; Gesamtwirtschaftliche Nachfrage; Inflation; USA